Pengaruh Rasio Fundamental Keuangan Terhadap Return Saham Perusahaan Sektor Kesehatan Yang Ada Di Bursa Efek Indonesia - Lilis Suryani; Neni Marlina Br. Purba (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
The stock returns of health sector companies experienced fluctuating changes but experienced many declines, this decline was caused by investor analysis in the form of Quick Ratio, Debt Equity Ratio, Net Profit Margin and Inventory Turnover. The purpose of this research is to determine the effect of Quick Ratio, Debt Equity Ratio, Net Profit Margin and Inventory Turnover on stock returns in health care companies. The type in this study is quantitative associative, the method used is documentation with SPSS 22 analysis, the tests carried out are classical assumption tests, multiple linear regression tests and also hypothesis testing with t-test and f-test. The sample is non-probability sampling consisting of companies in the health sector (healthy care) in 2016-2020. The results partially show that QR, DER, NPM and IT have a significant effect on return. Simultaneously QR, DER, NPM and IT affect the return with a value (13.543 > 2.74) and a significance value (0.005 < 0.05). In conclusion, H1 is accepted, H2 is accepted, H3 is accepted, H4 is accepted and H5 is accepted.